2005
DOI: 10.1108/09564230510592289
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of service attributes: a test of Kano's theory of attractive quality

Abstract: PurposeThe aim of the paper is to contribute to a better understanding of the theory of attractive quality through an empirical investigation of an e‐service. Our focus is on the consistency of different levels of service attributes and their dynamics. Our empirical investigation aims to increase both the validity of the theory of attractive quality and the use of technology readiness as a means to understand the variation of customer perceptions of service attributes.Design/methodology/approachA survey of cus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
130
1
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(141 citation statements)
references
References 26 publications
5
130
1
5
Order By: Relevance
“…Early work was conducted in the area of engineering (Kano, 1984). More recently, the Kano methodology, however, has also been applied successfully to diverse domains such as e-services (Nilsson- Witell & Fundin, 2005;Witell & Löfgren, 2007), employee satisfaction (Matzler et al, 2004a), bank services (Bhattacharyya & Rahman, 2004), internet community bonding (Szmigin & Reppel, 2004), and tourist satisfaction in Singapore (Pawitra & Tan, 2003).…”
Section: The Kano Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Early work was conducted in the area of engineering (Kano, 1984). More recently, the Kano methodology, however, has also been applied successfully to diverse domains such as e-services (Nilsson- Witell & Fundin, 2005;Witell & Löfgren, 2007), employee satisfaction (Matzler et al, 2004a), bank services (Bhattacharyya & Rahman, 2004), internet community bonding (Szmigin & Reppel, 2004), and tourist satisfaction in Singapore (Pawitra & Tan, 2003).…”
Section: The Kano Methodologymentioning
confidence: 99%
“…Nilsson- Witell & Fundin (2005) found that after using an e-service (online ordering of movie tickets) five or more times customers perceived the service as a one-dimensional or even must-be factor. Thus, taking a longitudinal approach, future research could investigate whether attributes of professors also deteriorate over time from excitement factors to one-dimensional attributes and finally to must-be factors.…”
mentioning
confidence: 99%
“…The Kano Model was first proposed by Kano et al in 1984, and relevant research employing the Kano model research method has been widely applied to product design, consumer behavior, community development and tourism services (Sireli et al, 2007;Ho and Lee, 2007;Nilsson-Witell and Fundin, 2005). It involves little mathematical computation and can be used to collect relevant information quickly.…”
Section: Applications Of the Kano Model And Ipamentioning
confidence: 99%
“…In studies of customer value and satisfaction, researchers have proposed that customer perceptions of service attributes will change over time (Nilsson-Witell and Fundin, 2005). Woodruff (1997) argued that important attributes perceived by customers will change with time, and when a product is in purchase, in use, and after use, the customers' perceived value for each attribute of a product will change.…”
Section: Dynamic View Of Attribute Importancementioning
confidence: 99%